A Self‐Assembled Bicontinuous Cubic Phase with a Single‐Diamond Network. Issue 22 (23rd April 2019) - Zeng, Xiangbing; Poppe, Silvio; Lehmann, Anne; Prehm, Marko; Chen, Changlong; Liu, Feng; Lu, Huanjun; Ungar, Goran; Tschierske, Carsten
Abstract: The first single‐diamond cubic phase in a liquid crystal is reported. This skeletal structure with the F d 3 ‾ m space group is formed by self‐assembly of bolaamphiphiles with swallow‐tailed lateral chains. It consists of bundles of π‐conjugated p‐terphenyl rods fused into an infinite network by hydrogen‐bonded spheres at tetrahedral four‐way junctions. We also present a quantitative model relating molecular architecture to the space‐filling requirements of six possible bicontinuous cubic phases, that is, the single‐ and double‐network versions of gyroid, diamond, and "plumber′s nightmare". Abstract : Liquid‐crystalline diamond : The first single‐diamond network is formed by self‐assembly in a soft‐matter system. In this cubic liquid‐crystalline phase with the F d 3 ‾ m space group, rod‐bundles replace the C–C bonds and polar spheres replace the carbon atoms of the diamond lattice.